Feasibility Analysis of Hydroponic Melon Business at PT. Agro Bergas Sejahtera, Bergas Subdistrict, Semarang Regency - Muhammad Ulyn Nuha; Agus Setiadi; Titik Ekowati (Quantitative Economics and Management Studies, 2024)
This research aims to analyze the feasibility of hydroponic melon business at PT. Agro Bergas Sejahtera. Data collection of the case study method was carried out in detail using various existing data collection procedures. Sampling was obtained from all twelve employees who recognize and have various information needed for the research to be carried out. The sampling technique employed interviews of all samples as respondents. Primary data included data obtained through direct interviews from sources in the field, such as resources, production, investment costs, and operating costs. Secondary data were data obtained indirectly from sources related to research, namely Central Bureau of Statistics (BPS) data and documents from PT. Agro Bergas Sejahtera. The data obtained was then analyzed using qualitative and quantitative analysis. Qualitative analysis is used to analyze non-financial aspects, including production aspects. Quantitative analysis was used to analyze the financial feasibility of PT. Bergas Agro Sejahtera using investment criteria, such as Payback Period, NPV, IRR, and Profitability Index. The research results indicate that hydroponic melon farming at PT. Agro Bergas Sejahtera is feasible according to the production aspect. The calculation results show that the payback period analysis is during two years four days. NPV is Rp. 637.561.973, IRR is 37%, and PI is 1,73. The financial analysis results show that all financial aspects are feasible.